Digitalização de acervo acadêmico: estudo de caso do setor de arquivo - DRCIN, do IFPA, Campus Belém - FARINHA, Brenda Thayná costa (2022)
With the insertion of technology in archivology, the way to produce, manage, process, store, preserve and make available the information in documents had completely changed. To help in the preservation and quickly and effective localization of the documents, it was necessary to use documents scanning processes. The Federal Institute of Pará must comply the Ordinance 315/2018 - MEC, which obliges the Higher Education Institutions to digitize their academic collection within a period of twenty-four months.To make this effective, it was necessary to use the resolutions numbers. 31, 43 and e-Arq Brasil of the National Archives Council (CONARQ). Thus, this research sought to discover the complexities of digitization as well as contribute to the preservation of the academic’s documents through field research with participant observations, interviews with Information Technology professionals and archivists, using as a research instrument a questionnaire to evaluate and identify the technological needs of the adequacy of the system used to manage the documents with eArq Brasil. As well as verify other digitization processes in federal entities in Brazil. Finally, a diagnosis was made in the archives sector to scale the planned work and, for this, were made two schedules: one for the digitization of the graduate and specialization documents and another for the other documents contained in the archive. In addition, were determined the tools for the implementation of digitization and were analyzed the EDM system for electronic management, aiming at the automation of the management of academic documents.